Book ‘Aplinkos apsauga keliuose’ review - Laurinavičius, A. (Journal of Environmental Engineering and Landscape Management, 2012)
"Book ‘Aplinkos apsauga keliuose’ review." Journal of Environmental Engineering and Landscape Management, 20(4), pp. 316-317 Article in Lithuanian.